PENGARUH KEPEMILIKAN INSTITUSIONAL, KEPEMILIKAN MANAJERIAL, AUDIT TENURE DAN KUALITAS AUDIT TERHADAP INTEGRITAS LAPORAN KEUANGAN - citra lestari; Julian Maradina (Publika Citra Media, 2026)
This study aims to analyze the effect of institutional ownership, managerialownership, audit tenure, and audit quality on the integrity of financial statements inbanking companies listed on the Indonesia Stock Exchange for the 2020–2024period. The integrity of financial statements is essential, as various manipulationcases highlight weaknesses in corporate governance practices in Indonesia.Thisresearch uses a quantitative approach with secondary financial statement data.Panel data regression is applied using the Chow, Hausman, and Lagrange Multipliertests to determine the best model. The results show that simultaneously all variablesaffect financial statement integrity. Partially, managerial ownership and auditquality have a positive and significant effect, while institutional ownership and audittenure show no significant effect.This study is expected to provide insights intofactors influencing financial statement integrity and serve as a reference forcompanies and auditors in improving governance practices.